Efek latihan plyometric pada kekuatan otot tungkai pada pemain bola voli - Novita, Novita; Oka Harahap, Putra; Sahputera Sagala, Ramlan; Natas Pasaribu, Ahmad Muchlisin (Universitas Nusantara PGRI Kediri, 2022)
The necessity of power in volleyball is to support the game's technique. Volleyball players' leg muscles must be strong enough to sustain techniques like smashes, blocks, and serves. Proper workouts, such as plyometric exercises, should reinforce the importance of muscular leg power. This study aims to determine the impact of plyometric side-to-side box shuffle and leap to box exercises on leg muscle power and determine which workouts are more successful in developing volleyball participants' limb muscular explosiveness. This is an experimental study with a